Molecular and biochemical characterization of galectin from amphioxus: primitive galectin of chordates participated in the infection processes - Yu, Yanhong; Yuan, Shaochun; Yu, Yingcai; Huang, Huiqing; Feng, Kaixia; Pan, Minming; Huang, Shengfeng; Dong, Meiling; Chen, Shangwu; Xu, Anlong (Glycobiology (Oxford), 2007)
A novel F4-carbohydrate recognition domain (CRD)-linker-F3-CRD-type bi-CRD Branchiostoma belcheri tsingtauense galectin (BbtGal)-L together with its alternatively spliced mono-CRD isoform BbtGal-S from amphioxus intestine was encoded by a 9488-bp unique gene with eight exons and seven introns. The recombinant proteins of BbtGal were found to have β-galactoside-binding activity, indicating that BbtGal was a member of the galectin family. Phylogenetic analysis of this gene along with its splicing form and genome structure suggested that the BbtGal gene was the primitive form of the chordate galectin family. Real-time polymerase chain reaction analyses (PCR) indicated that BbtGal mRNA was expressed during all stages of embryonic development. In terms of tissue distribution, BbtGal-L mRNA was mainly expressed in the immunity-related organs, such as hepatic diverticulum, intestine, and gill, but BbtGal-S was ubiquitously expressed in all tissues. The expression of BbtGal-L mRNA was elevated after acute challenge with various microorganisms, but BbtGal-L only bound to specific bacteria. The immune function of BbtGal was consistent with its localization both outside and inside the cell. Our study on amphioxus galectin may help further understanding of the evolution of chordate galectin in terms of host-pathogen interaction in the immune system.